Azobenzene-modified DNA aptamers evolved by capillary electrophoresis (CE)-SELEX method. (1st January 2021) - Morihiro, Kunihiko; Hasegawa, Osamu; Kasahara, Yuuya; Mori, Shohei; Kasai, Tatsuro; Kuwahara, Masayasu; Obika, Satoshi
Graphical abstract: Abstract: Chemically modified aptamers have recently emerged as important materials for nucleic acid based therapeutics and diagnostic tools. Here, we report in vitro evolution of azobenzene-modified DNA aptamers by capillary electrophoresis (CE)-SELEX method. Azobenzene has been considered to be a fascinating functional group due to its trans – cis photo-isomerization property. We harnessed C5-azobenzene-modified 2′-deoxyuridine (dU Az ) as a azobenzene-tethered unit and subjected it to CE-SELEX with human thrombin. The obtained dU Az -modified aptamer showed strong binding affinity toward human thrombin and could be reversibly photo-isomerized by different wavelengths of light. This work demonstrates that CE-SELEX is a powerful method to obtain chemically modified aptamers and dU Az is an excellent photo-responsive nucleoside for nucleic acid photo-switches.